In vitro and in vivo characterization of SARS-CoV-2 resistance to ensitrelvir - Kiso, Maki; Yamayoshi, Seiya; Iida, Shun; Furusawa, Yuri; Hirata, Yuichiro; Uraki, Ryuta; Imai, Masaki; Suzuki, Tadaki; Kawaoka, Yoshihiro (Nature communications, 2023)
Ensitrelvir, an oral antiviral agent that targets a SARS-CoV-2 main protease (3CLpro or Nsp5), is clinically useful against SARS-CoV-2 including its omicron variants. Since most omicron subvariants have reduced sensitivity to most monoclonal antibody therapies, SARS-CoV-2 resistance to other antivirals including main protease inhibitors such as ensitrelvir is a major public health concern. Here, repeating passages of SARS-CoV-2 in the presence of ensitrelvir revealed that the M49L and E166A substitutions in Nsp5 are responsible for reduced sensitivity to ensitrelvir. Both substitutions reduced in vitro virus growth in the absence of ensitrelvir. The combination of the M49L and E166A substitutions allowed the virus to largely evade the suppressive effect of ensitrelvir in vitro. The virus possessing Nsp5-M49L showed similar pathogenicity to wild-type virus, whereas the virus possessing Nsp5-E166A or Nsp5-M49L/E166A slightly attenuated. Ensitrelvir treatment of hamsters infected with the virus possessing Nsp5-M49L/E166A was ineffective; however, nirmatrelvir or molnupiravir treatment was effective. Therefore, it is important to closely monitor the emergence of ensitrelvir-resistant SARS-CoV-2 variants to guide antiviral treatment selection. Ensitrelvir is an oral antiviral agent that targets SARS-CoV-2 and is clinically useful against infection with omicron variants. The authors characterized mutant viruses with reduced sensitivity to ensitrelvir in vitro and in vivo.